DEVELOPMENT OF SOIL FERTILITY MAP BY GIS TECHNOLOGY FOR WUKARI LOCAL GOVERNMENT AREA OF TARABA STATE - Yakub, Waizah (FUDMA Journal of Sciences, 2026)
Soil fertility mapping is critical for site-specific nutrient management as it gives information about soil nutrient content, which is vital for land use, site-specific management, fertilizer recommendations, and sustainable management of soil resources. Semi-detailed soil survey was carried out in Wukari Local Government Area to establish a soil fertility map. A coordinated data collection was designed using GIS in such a way that the entire LGA was divided into grids of 155 blocks, out of which a total of 98 augured samples were collected at the depth of 0-25 cm. All samples collected were analyzed following standard analytical procedures. ArcGIS was used in the creation of the models. The ordinary Kriging interpolation was adopted for soil mapping. Semivariogram analysis fitted into the Gaussian model was used to test the spatial dependence of the soil parameters. Spatial distribution maps were developed with sub-models of 10 classes of raster values; the values of this element were then regrouped based on the documented standards to produce soil nutrient maps showing areas of low, medium, and high concentration. A general soil fertility map was developed using fertility expert judgement based on the contribution of some key fertility elements (pH, N, P, K, S, OC, ECEC, Mn, Zn, and Fe), and the nutrient maps earlier reclassified were combined based on the weighted overlay model in ArcGIS 10.5 to produce one single fertility map with four classes:
Keywords: Kriging; spatial distribution; mapping; fertility